Pemberdayaan Petani Tembakau melalui Diskusi Konservasi Tanah dan Air di Desa Kwadungan Gunung - Kautsar, Valensi; Tarmadja, Samsuri; Ismiasih, Ismiasih; Ferhat, Amallia (Empowerment, 2024)
Kwadungan Gunung Village, located in Kledung Sub-district, Temanggung Regency, is a region characterized by its agricultural nature and sloping topography. This results in a significant risk of soil and water damage owing to erosion. The survey and land analysis indicate that erosion has transpired in many locations, ranging from low to medium severity. Furthermore, numerous constraints imposed by farmers suggest that there is a relatively restricted supply of water during the dry season. Hence, it is imperative to implement genuine measures for soil and water conservation. The primary goal of this empowerment is to enhance the comprehension and implementation of soil and water conservation practices among local farmers. The aim is to ensure that the agricultural cultivation business in Kwadungan Gunung Village operates in a sustainable. Initially, discussing sessions on soil and water conservation were carried out in partnership with the local government of Kwadungan Gunung Village. Result showed that farmers have applied conservation measures, albeit to a limited scale. The favorable reception of the extension initiatives indicates the capacity to enhance the use of conservation practices. Subsequently, a demonstration plot will be created to showcase soil and water conservation measures. This plot will function as a tangible example for farmers and will also be included in the farm evaluation process. This demonstrates the unwavering dedication of the agricultural community to the principles of sustainable farming and environmental preservation.